2014
DOI: 10.1007/s13277-014-1739-x
|View full text |Cite
|
Sign up to set email alerts
|

EGFR signaling-dependent inhibition of glioblastoma growth by ginsenoside Rh2

Abstract: Glioblastoma is the most common and most aggressive malignant primary brain tumor in humans, accounting for 52 % of all functional tissue brain tumor cases and 20 % of all intracranial tumors. The typical treatment involves a combination of chemotherapy, radiation, and surgery, whereas it still achieves fairly poor patient survival. Ginsenoside Rh2 has been reported to have a therapeutic effect on some tumors, but its effect on glioblastoma has not been extensively evaluated. Here, we show that ginsenoside Rh2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 28 publications
3
43
0
Order By: Relevance
“…In previous studies, it was found that ginsenoside Rh2 down-regulated EGFR and recombinant EGFR reduced anticancer activity of ginsenoside Rh2 in glioblastoma [29]. Ginsenoside Rh2 inhibited the growth of glioblastoma by binding EGFR competitively against EGF, and by inactivating EGFR/PI3k/Akt/mTOR signaling.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, it was found that ginsenoside Rh2 down-regulated EGFR and recombinant EGFR reduced anticancer activity of ginsenoside Rh2 in glioblastoma [29]. Ginsenoside Rh2 inhibited the growth of glioblastoma by binding EGFR competitively against EGF, and by inactivating EGFR/PI3k/Akt/mTOR signaling.…”
Section: Discussionmentioning
confidence: 97%
“…Ginsenoside Rh2 (GRh2) is a well-characterized component in red ginseng, and has definite therapeutic effects on inflammation [11], abnormal vascularization [12], and some cancers [13][14][15][16], although the underlying mechanisms are still ill-defined. Nevertheless, whether GRh2 may be an effective treatment for pediatric leukemia has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Since growth of GBM accounts for its major malignancy and detrimental effects on patients [1,2,3,4,5], here we aimed to elucidate the precise downstream signaling of an activated TGFβ receptor signaling on the growth of GBM cells [6,7,8,9,10,11,12,22,23,24,25,26,27,28,29,30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM), which is named as glioblastoma by WHO, is the most common and most malignant primary brain cancer in humans [1,2,3,4,5]. GBM is originated from glial cells and the patients suffer from an extremely low five-year survival ratio, which reasons from the relatively high invasiveness of GBM and the location of the tumor in the relatively closed central nervous system [1,2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation